First you must find a common denominator. In this case 10 will work. You then multiply the top number by whatever you multiplied the bottom number by. This is shown below:
4/5- 3/10 = 8/10- 3/10
You can now solve this to get 5/10. This answer can then be reduced to 1/2.
7-4x=2-9x the answer is x=1
Set up a system of equations.
X+y=6
Y-x =40
Substitution method.
Y=6-x
(6-x)-x =40
6-2x=40
-2x=34
X= -17
Plug it back into the equation.
-17+y=6
Y=33
(-17,33) is one of the possible answers.
Answer:
x=-27, y=-15
Step-by-step explanation:
In the attached file
Answer:
D.
Step-by-step explanation:
-2*-3=6 -2*5=-10. -2*1=-2
-2*8=-16. -2*-2=4. -2*3=-6
-2*2=-4. -2*1=-2. -2*-4=8